Application of microbial cross-over for the production of Italian grape ale (IGA), a fruit beer obtained by grape must addition. (April 2023) - Siesto, Gabriella; Pietrafesa, Rocchina; Tufariello, Maria; Gerardi, Carmela; Grieco, Francesco; Capece, Angela
Abstract: In the last years, the production of grape ale beer has become a trendy choice among brewers in Italy, resulting in a new beer type known as Italian Grape Ale (IGA), a sort of bridge beverage between beer and wine. In this study, three autochthonous Saccharomyces cerevisiae strains (CHE-3, P4 and TA4-10), previously isolated from different food types, were tested in comparison with the commercial strain US-05. Fermentations were conducted at a laboratory scale on malt extracts with 15% and 25% grape must adjuncts, and on malt wort (control). After fermentation, the CHE-3, P4 and TA4-10 strains showed significantly higher CO2 production than US-05. The main analytical parameters (organic acids, real and apparent attenuation, ethanol content, glycerol level and carbohydrate profile) and the volatile compounds related to the organoleptic quality of the experimental beers were strongly influenced both by the grape must addition to the fermentation medium and the used strains. The addition of grape must enhanced the CO2 production, especially when 25% of grape must was added to the wort. By comparing the tested strains, the highest aromatic expression was observed with 15% grape must adjunct. The present results confirm the importance of media composition and microbial biodiversity to gain more different beers especially in the craft beers sector. Moreover, the outcome data show the significance of microbial cross-over, a novel approach based on the exploitation of microorganisms traditionally used in other agro-food chains also for brewing novel beer types.